Biosorption and Transformation of Tetra-Chloroethylene and Trichloroethylene Using Mixed-Species Microbial Mats - W. L. O'Niell; V. A. Nzengung; J. E. Noakes; J. Bender; P. C. Phillips (Journal of Hazardous Substance Research, 1999)
Microbial mats are naturally occurring assemblages of aquatic organisms capable of sorbing and degrading various organic compounds. Kinetic transformation and sorption experiments were conducted in sealed batch vials, using microbial mats dosed with unlabeled tetrachloroethylene (PCE) and trichloroethylene (TCE) and radiolabeled forms of these compounds ([14C]PCE and [14C]TCE). Results indicated that sorption equilibrium was attained for both chemicals within a few hours. The sorption isotherm was linear, demonstrating that the sorption mechanism was partitioning. PCE was completely degraded in periods as short as 50 days under favorable growth conditions. Samples were also tested for degradation products, with analyses indicating that PCE and TCE are transformed through both aerobic and anaerobic pathways. The ability of the microbial mats to sorb and degrade PCE and TCE suggests a potential for their application to the bioremediation of media contaminated by these compounds.
Keywords: tetrachloroethylene; trichloroethylene; partitioning; biosorption; microbial mats